The Antioxidant Activity of Caesalpinia sappan L. Heartwood - Wetwitayaklung, Penpun; Phaechamud, Thawatchai; Keokitichai, Sindhchai (Asian Health, Science and Technology Reports, 2005)
The heartwood of Caesalpinia sappan L. (Caesalpiniaceae) is traditionally used in China and Ayurveda. In Thailand it is used as coloring agent in beverage, food, garment and cosmetics. The objective of this study is to find out which ages of wood giving effective natural antioxidant. The heartwood extracts in various ratio of extraction solution CH3OH:CH2Cl2 and various ages were measured for the amount of brazilin and antioxidant activity. The antioxidant activity was obtained by trolox equivalent antioxidant capacity (TEAC) assay. The CH3OH:CH2Cl2 (1:3) was the best ratio for extraction solution and gave extracts with high amount of brazilin and antioxidant property. The older heartwood had higher quantities of antioxidant activity. The ages of the heartwood was not an important factor for amount of brazilin and its derivatives.